Effect of olive leaf extract marination on heterocyclic aromatic amine formation in pan‐fried salmon. (11th January 2022) - Macit, Arife; Kizil, Mevlude
Abstract: BACKGROUND: In this study, the reducing effects of varying levels of olive leaf extract (0%, 0.25%, 0.5%, 1% and 2%) on the formation of heterocyclic aromatic amines (HAAs) in pan‐cooked salmon at 180 and 220 °C were examined. RESULTS: All salmon samples were analyzed for ten HAAs: IQx, IQ, MeIQx, MeIQ, 4, 8‐DiMeIQx, 7, 8‐DiMeIQx, PhIP, AαC, MeAαC and Trp‐P‐2. The most abundant HAA was MeIQ (≤2.98 ng g −1 ) followed by Trp‐P‐2 (≤2.40 ng g −1 ), MeIQx (≤0.83 ng g −1 ), IQ (≤0.41 ng g −1 ), 7, 8‐DiMeIQx (≤0.29 ng g −1 ), 4, 8‐DiMeIQx (≤0.16 ng g −1 ) and IQx (≤0.06 ng g −1 ). However, PhIP, AαC and MeAαC were undetectable in all samples. In the control samples, HAAs were found at levels ranging from not detected to 2.40 ng g −1 . Total HAA content was between 0.81 and 4.03 ng g −1 . The olive leaf extracts reduced the total HAA levels at all certain concentration levels at 180 °C and the reducing effects were found to be 32.78–77.69%. CONCLUSION: The current study displayed that olive leaf extracts could be efficient when added in up to 1% concentration prior to cooking for reducing HAA formation without changing organoleptic characteristics of salmon. © 2021 Society of Chemical Industry.